Formulasi, Evaluasi, dan Stabilitas Sediaan Sirup Paracetamol: Formulasi, Evaluasi, dan Stabilitas Sediaan Sirup Paracetamol - Sasaqi, Adzkia Pratami; Nggiring, Maria Imaculata Sherly; Apriyanti, Nita; Permata Sari, Aulia; Nurholisa, Neng Dera Siti; Saputro, Ramadhan; Pratama, Reza (LP4M STIKes Karsa Husada Garut, 2025)
Introduction: Paracetamol syrup is a commonly used oral liquid dosage form, especially for pediatric patients. Its physical and chemical stability is strongly influenced by formulation and storage conditions. This review aims to analyze the formulation, quality evaluation, and stability of paracetamol syrup based on several studies. Literature searches were conducted through Google Scholar, PubMed, and ResearchGate using keywords such as “paracetamol syrup stability,” “accelerated stability test,” and “formulation of paracetamol syrup.” Paracetamol syrup generally contains 125 mg/5 mL of the active ingredient, with propylene glycol and glycerin as cosolvents to enhance solubility and stability. Sweeteners such as sucrose or honey improve taste and maintain viscosity, while flavors increase acceptability for pediatric use. Evaluation results show that most formulations met physicochemical requirements, with pH values between 4.5–5.5, viscosity ranging from 1800–2200 cP, and paracetamol content above 90% of the initial amount. In both accelerated (40°C/75% RH) and long-term (25°C) stability tests, the formulations remained chemically stable with degradation less than 10%. High temperatures or light exposure increased degradation, while storage at room temperature in amber bottles ensured optimal stability. The use of propylene glycol as a cosolvent and citrate buffer as a stabilizing agent provided good physical and chemical stability. All reviewed formulations fulfilled Indonesian Pharmacopoeia requirements, with the best stability achieved when stored at room temperature and protected from light. Keywords: paracetamol, syrup, formulation, accelerated stability, evaluation test